Do tax officials use double standards in evaluating citizen‐clients? A policy‐capturing study among Dutch frontline tax officials. (12th November 2017) - Raaphorst, Nadine; Groeneveld, Sandra; Van de Walle, Steven
Abstract : In line with psychological and economic discrimination theories, street‐level bureaucracy studies show a direct effect of citizen characteristics on officials' judgements, or show how street‐level bureaucrats employ stereotypical reasoning in making decisions. Relying on sociological double standards theory, this study hypothesizes that citizen‐clients' status characteristics influence officials' evaluations not only directly, but also indirectly and more pervasively by influencing the interpretation of other signals. By means of a policy‐capturing study among Dutch frontline tax officials, this study takes a first step in testing double standards propositions in the context of official–citizen encounters. The findings support only some hypotheses, but indicate that citizen‐clients' level of education could serve as a moderating context affecting the interpretation of cues. The article provides important theoretical and methodological guidelines for future research on stereotyping at the front line.